ANALISIS STRUKTUR DAN KINERJA PEMASARAN JAMBU METE DI KECAMATAN TANJUNG BUNGA KABUPATEN FLORES TIMUR - Katarina S Luron; D. Roy Nendissa; Maria Bano (Buletin Ilmiah Impas, 2023)
This research has been carried out in the Tanjung Bunga District, Flores Timur Regency. The study was intended to analyze the structure and performance of the guava marketing. The study of guava farmers and the marketing agencies involved in guava marketing of farmers as island based producers and traders as consumers. The purpose of this study were (1) knowing the structure of the guava market as represented, and (2) knowing how guava market performance is portrayed in Distric Tanjung Bunga, Flores Timur Regency, the sampling technique used for the peasant responders used the simple random sampling technique while for the merchant responders used the snowball sampling. economic analysis that is the calculation of Farmers' Share, Margins, and profits of marketing costs. The results of this study indicate that the guava market structure is quantitatively that market structure in Tanjung Bunga District, Flores Timur Regency to the imperfect competitive market or the oligopsony, and market performance in Tanjung Bunga District, Flores Timur Regency forms a two channel marketing which is channel one Farmers→PPK (Collecting Collectors District) → PAP (Interisland Merchants), two channel Farmers → PAP (Interisland Merchants). The highest margin marketing on channel two, The Farmer Share is shared on channel one and two which is the same and the marketing has the most to gain in channel two.